Integrated coastal zone management in Vietnam - status and emerging problems - Cong, Nguyen Van; Thạnh, Tran Duc; Nhon, Dang Hoai (Vietnam Journal of Marine Science and Technology, 2020)
ICZM is a correct orientation and feasible towards sustainable development. Due to socio- economic circumstances, there are certain differences in the application of ICZM model in different countries, especially in the developed and developing countries. Although there were successful models in some countries or some places, many activities of ICZM do not achieve high efficiency and do not become a self-reliant process. ICZM in Vietnam has achieved certain results. Over the past 20 years, research projects, pilot projects and implementation projects have significantly contributed to ICZM in terms of improving knowledge, increasing awareness and accumulating experience. Vietnam has a favorable organizational mechanism for ICZM, which is considered as an indispensable orientation for sustainable development. ICZM in Vietnam has a solid legal basis. However, ICZM in Vietnam is not very sustainable, facing great opportunities and challenges. ICM is facing issues that need to be addressed such as theoretical basis, organizational structure, capacity, methodology and sustainable financial resources,... ICZM can only succeed on the basis of mastering the theoretical basis and having creative application in practical conditions of Vietnam